The law of child witness in Malaysia: a reform proposal of the evidence of child witness act 2007 (act 676) / Ameera Mastura Khamis...[et al.] - Khamis, Ameera Mastura; Abd Aziz, Amira; Mohd Isa, Sara Aisha (2011)
This research analysed the weaknesses of the Evidence of Child Witness Act 2007 (Act 676) and to give recommendations with the intention to reform on the weaknesses of the said Act. The first chapter goes into the essence and structure of the research. All the necessary conceptual features are introduced to ensure the readers to understand about the research. The second chapter focused on the content of Act 676 which was analysed by the researchers entirely. In the third chapter, the researchers pointed out some relevant issues of evidence of a child which consists of general principle of corroboration of child witness, nature of oath and issues and problems associated with child witness. The fourth chapter discussed on the findings based on the interview conducted. Our research concludes with the proposal to amend and reform the Evidence of Child Witness Act 2007 (Act 676) and some other recommendations to improve the evidence by child witness as well as the law in regards to child witness.